First rain and cloud measurement by FMCIW 35 GHz radar in Prague - Pitaš, Karel; Fišer, Ondřej (IEEE (Institute of Electrical and Electronics Engineers), 2019)
Institute of Atmospheric Physics Prague is finishing modern semiconductor cloud Doppler radar PCDR 35 of the FMICW type. This radar is briefly described. This contribution deals with first actual measurement of atmospheric targets. Firstly measurement of clutters, then measurement of rain volume and rainy clouds is presented. The received power was re-computed into widely used meteorological quantity “radar reflectivity factor Z” and also equivalent rain rate was estimated. First results are promising.
První měření deště a oblačnosti radarem FMCIW 35 GHz v Praze
Keywords: Clouds, Meteorological radar, Radar measurements, Terrestrial atmosphere; Oblačnost, Meteorologický radar, Radarové měření, atmosféra